Effect of Kuniran Fish Meat Flour (Upeneus moluccensis) Substitution on Kastengel Organoleptic Aspects - Mukti, Annisa Estu; Laili Hidayati,; Issutarti, (Jurnal Sains Boga, 2023)
Kastengel is a pastry that has a characteristic savoury taste that comes from cheese. This snack is made from a mixture of flour, eggs, butter/margarine, edam cheese and cheddar cheese. The substitution of yellow goatfish meal aims to add innovation to kastengel, increase fish consumption, and increase the economic value of yellow goatfish fish. The purpose of this study was to determine the effect of Kastengel substitution of turmeric fish meal with percentages of 15%, 20%, and 25% on the organoleptic properties of colour, taste, and aroma. This research is an experimental study using a completely randomized design (CRD) method with one repetition with 100 panellists. The panellists involved were untrained panellists. Data analysis using ANOVA with DMRT follow-up test. Determination of the best formulation using an effectiveness index based on organoleptic properties parameters including hedonic quality tests (colour, taste, and aroma) and hedonic properties tests hedonic quality tests (colour, taste, and aroma). The results showed that the substitution of yellow goatfish with different percentages had an effect on the quality and level of preference for the aroma and taste of kastengel, but had no effect on the quality and level of preference for the colour of kastengel. The results of the best formula of kuniran fish kastengel is the substitution of 15%yellow goatfish meat meal 0.82.